A dihydro-β-agarofuran sesquiterpene from Maytenus boaria - Paz, Cristian (2017)
The natural compound (1S,4S,5S,6R,7R,8R,9R,10S)-6-acetoxy-4,9,10-trihydroxy-2,2,5a,9-tetramethyloctahydro-2H-3,9a-methanobenzo[b]oxepin-5-yl furan-3-carboxylate, C22H30O9, (I), is a β-agarofuran sesquiterpene isolated from the seeds of Maytenus boaria as part of a study of the secondary metabolites from Chilean flora. The compound presents a central structure formed by a decalin system esterified with acetate at site 1 and furan-3-carboxylate at site 9. The chirality of the skeleton can be described as 1S,4S,5S,6R,7R,8R,9R,10S, which is consistent with that suggested by NMR studies. Unlike previously reported structures of sesquiterpenes containing a pure dihydro-β-agarofuran skeleton, (I) exhibits a three-dimensional hydrogen-bonded network.